Model Peningkatan E-Satisfaction Berbasis Online Shopping Experience dan Customer Engagement Konsumen Shopee di Kota Jambi - Susilawati, Susilawati; Sopini, Pupu; Syukri, Muhammad (Universitas Batanghari Jambi, 2024)
This research aims to analyze a model for increasing e-satisfaction based on online shopping experience and online customer engagement for Shopee marketplace consumers in the city of Jambi. The choice of Shopee e-commerce is one of the marketplaces that is developing in the digital industry in Indonesia. This research uses quantitative descriptive methods with the population of the city of Jambi in 2021, namely 612,162 people. The number of samples was determined based on the Slovin formula used, that the number of samples used in this research was 100 respondents. The analytical tools used are the Likert scale and multiple linear regression. The research results reveal that the better the online shopping experience and online customer engagement, the higher the e-satisfaction of Jambi city Shopee marketplace consumers. Simultaneously and partially, the online shopping experience and online customer engagement variables have a significant effect on shopee marketplace consumer e-satisfaction in the city of Jambi.